The Influence of Physical Loads of the Average and Submaximal Level on the Structure of the Neurons of the Spinnasic Node - Sergii Popel'; Bohdan Mytckan (Lesya Ukrainka Volyn National University, 2017)
The purpose of the study is to study the character of the ultrastructural rearrangement of the components of the spinal node under the influence of the physical load of the average aerobic capacity. The power of physical exercise (running in the treadmill) was 70 % of the maximum oxygen absorption. The cellular component of the spinal node reacts to the physical load with nonspecific manifestations and depends on the type of neurons. In an experiment on laboratory rats, it was shown that the period of normalization of the constituent components of the spinal node after hypokinesia depends on the number of sessions of physical activity. After five sessions there are changes in the organelle in the light neurons, which ensures the transition of neurons to a new level of functioning. After 10 sessions, the physical load causes an increase in changes in the cytoplasmic structures in the neurons and acquires a generalized character, which is a nonspecific adaptive response to external influences, which leads to the formation of a structural and functional adaptation trace of the cells necessary to enhance energy supply. The increase in the effect of physical activity up to 15 sessions causes structural rearrangement also in dark neurons, which provides high speed and reverse functional changes. Increasing the physical load up to 30 sessions leads to a rearrangement of the glial component, which leads to an improvement in trophic neurons. The formation of a long-term structural traces of adaptation is associated with an early and pronounced response of blood vessels in the spinal nodes.